HOAXES AND DEFAMATION: LEGAL LIMITATIONS IN ASSESSING NON-MATERIAL DAMAGES - Annazali, Ahmad Haqqi; Marsal, Irsyaf; Syarkun, Mufarikha Binti (Yayasan Pendidikan Islam Almatani, 2025)
The rapid spread of hoaxes and defamation in the digital age has become a destructive phenomenon, causing serious consequences that include not only material losses, but also significant non-material damages such as ruined reputations, loss of public trust, and profound psychological suffering for both individuals and corporations. This condition creates a crucial juridical problem because positive law in Indonesia, despite having instruments like the ITE Law, has not yet provided clear boundaries (limitations) or objective, measurable parameters for assessing and quantifying such non-material damages within the judicial system. This research utilizes a normative legal method employing a statute approach and a conceptual approach, qualitatively analyzing primary legal sources such as the Civil Code, Criminal Code, the ITE Law and its amendments, as well as secondary legal sources through a comprehensive literature review. The results and discussion demonstrate that the forms of non-material damage, as recognized in Article 1365 of the Civil Code and legal theory, encompass a broad spectrum ranging from damage to honor (eer) and good name (goede naam) to psychological suffering (trauma and stress); however, the legal boundaries in Indonesia are dominantly penal-centric, focusing only on punishing the perpetrator (deterrence) rather than restoring the victim. This strong penal orientation in the ITE Law is proven to create systemic fragmentation separating the criminal and civil processes and a legal vacuum (rechtsvacuüm) in non-material remediation mechanisms, thereby necessitating a paradigm shift towards restorative justice supported by Supreme Court Guidelines (PERMA) to provide clear parameters for judges to assess non-material damages fairly and proportionally.